Chapter Comparative Adult and Continuing Education: A Guiding Essay - Egetenmeyer, Regina (Studies on Adult Learning and Education, 2020)
This paper provides a guide for developing a research design for comparative studies in adult and continuing education. To that end, a research methodology will be presented that was developed at the COMPALL and INTALL Winter Schools on Comparative Studies in Adult Education and Lifelong Learning. Central elements for systematic comparisons in adult and continuing education are (1) the object of comparison, (2) research fields for comparison, and (3) inductive comparative categories. These elements form the reference points for the development of a comparative research question in adult and continuing education. The comparative analysis proposes a three-step approach from juxtaposition to interpretation: step 1 - descriptive juxtaposition; step 2 - analytical juxtaposition; and step 3 - analytical interpretation.